Uma nova abordagem na utilização de ferramentas computacionais no ensino de conteúdos da disciplina estruturas de concreto em cursos de Engenharia Civil - Faria, Antonio de (2009)
This presentation analyzes the two computational tools, GPLAN (Plan Grills) and FTOOL (Two-Dimensional Frame Analysis Tool), and how they can be used in the content of "Concrete Structures" discipline, in Civil Engineering Graduation. The considered study is divided in two topics, being the first, the plan grills consideration (interaction plate/ beam) in the analysis of buildings floors to determine efforts and displacement, in comparison with the traditional teaching that considerate the elements in a isolated form, with the beams study through the theory of plates. The second topic refers to the porch plan consideration (interaction beam / pillar) for the lateral wind action consideration on buildings structures, and its efforts and displacements in order to analyze the instability parameter and the increase coefficient of the vertical actions z, provided by NBR 6118:2003. Thus, this study presents, in a didactic form, how the using of such tools can contribute to a civil engineer graduation regarding concrete structures, indicating through some examples, a variety of details and concepts that can be obtained through these tools. Finally, it is shown also that, to conduct checks according to the recent regulatory requirements, makes essential the use of computational tools, instead of manual methods.